Factors Contributing to the Success of Industrial Work Practice (PKL) Using PLS in a Vocational Mechanical Engineering Program - Jimmi Zamora; Arwizet K; Waskito; Giatman (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the factors that influence the success of Industrial Work Practice (PKL) implementation in the Mechanical Engineering Program at SMK Negeri 1 Sumatera Barat. Using a quantitative research design with Partial Least Squares (PLS), data were collected from 58 students who participated in the 2023 internship program. The research investigates the contribution of five variables: productive subjects, general subjects, curriculum alignment, school mentoring, and industrial mentoring. The findings show that productive subjects have the strongest influence on PKL success, followed by school mentoring and industrial mentoring. In contrast, general subjects and curriculum alignment do not demonstrate a significant effect. These results highlight the crucial role of technical competence and consistent guidance in ensuring effective internship experiences. The study emphasizes the need for stronger collaboration between schools and industry to enhance the relevance of vocational learning. It also suggests aligning instructional practices with workplace expectations to better prepare students for real industrial environments. Overall, this research provides empirical evidence that reinforces the importance of practical skills and structured mentoring in improving internship outcomes within vocational education.